Phylogenetic analysis of Notalina (Neonotalina) Holzenthal (Trichoptera: Leptoceridae), with the description of two new species from southeastern Brazil - Calor, Adolfo R.; Holzenthal, Ralph W.; Amorim, Dalton S. (Zootaxa, 2006)
Two new species of Notalina (Neonotalina) Holzenthal 1986 from southeastern Brazil are described and illustrated, N. (Neonotalina) froehlichi Calor & Holzenthal and N. (Neonotalina) paulista Calor & Holzenthal. Phylogenetic analyses confirm the placement of the nine Neotropical species of Notalina into two species groups, the roraima species-group and the brasiliana speciesgroup, with northern South American and southeastern Brazilian patterns of distribution, respectively. Additional collection records of previously described species from Brazil are provided.